2009
DOI: 10.1016/j.freeradbiomed.2008.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Altered redox status accompanies progression to metastatic human bladder cancer

Abstract: The role of reactive oxygen species (ROS) in bladder cancer progression remains an unexplored field. Expression levels of enzymes regulating ROS levels are often altered in cancer. Search of publicly available micro-array data reveals that expression of mitochondrial manganese superoxide dismutase (Sod2), responsible for the conversion of superoxide (O 2 -. ) to hydrogen peroxide (H 2 O 2 ), is consistently increased in high grade and advanced stage bladder tumors. Here we aim to identify the role of Sod2 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 50 publications
6
113
0
Order By: Relevance
“…Another interpretation is that the expressions of MMP-9 and vascular endothelial-derived growth factor (VEGF), an ascertained metastasis-related factor by promoting angiogenesis, were shown to be H 2 O 2 -dependent. Increased SOD2 expression was found to be accompanied by a significant decrease in catalase (CAT) activity, resulting in a net increase in H 2 O 2 production in cells (Hempel et al, 2009). In addition, the high level of SOD2 led to oxidative inactivation of PTEN (phosphatase and tensin homolog deleted from chromosome 10) and resulted in activation of Akt/PI3K signals, and consequently up-regulated the expression of VEGF (Connor et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interpretation is that the expressions of MMP-9 and vascular endothelial-derived growth factor (VEGF), an ascertained metastasis-related factor by promoting angiogenesis, were shown to be H 2 O 2 -dependent. Increased SOD2 expression was found to be accompanied by a significant decrease in catalase (CAT) activity, resulting in a net increase in H 2 O 2 production in cells (Hempel et al, 2009). In addition, the high level of SOD2 led to oxidative inactivation of PTEN (phosphatase and tensin homolog deleted from chromosome 10) and resulted in activation of Akt/PI3K signals, and consequently up-regulated the expression of VEGF (Connor et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the severity of invasion was directly correlated with SOD2 expression levels in fibrosarcoma cells and bladder tumor cells (Connor et al, 2007). Expression of SOD2 was consistently increased in high-grade and advanced-stage bladder tumors (Hempel et al, 2009). Activity of SOD2 was significantly higher in advanced-stage tumor or tumor with nodal metastasis in the head and neck squamous cell carcinoma (HNSCC) (Salzman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we also observed that most bladder cancer cells show enhanced ROS generation compared with control bladder cells (Supplemental Figure 2A). In bladder cancer, it was recently reported that the acquisition of metastatic ability is associated with the level of ROS scavenging enzymes in the bladder cancer cell lines 253J (non-metastatic) and 253J-BV (highly metastatic) (Hempel et al, 2009). However, no direct evidence that NOX-derived ROS are responsible for cell survival has been reported in bladder cancer cells although recently we observed that BLT2-linked ROS generation by NOX1 and NOX4 plays a role of bladder cancer invasion (Kim et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, an increase in superoxide dismutase and a decrease in catalase activities were found in epithelial tumour cells and in human melanoma cells. In this sense, a correlation between the endogenous levels of H 2 O 2 and the degree of malignancy was demonstrated in epithelial tumour cell lines from skin, breast and bladder (Hempel et al, 2009;Policastro el al, 2004). These characteristics further perpetuate a state of oxidative stress in cancer cells.…”
Section: Role Of Reactive Oxygen Species In Cancermentioning
confidence: 97%